INDUSTRIALIZATION AND TRANSPORT IN INDONESIA ON ENVIRONMENTAL DEGRADATION - Galih Ramadhan Febrianto; Hastarini Dwi Atmanti (TRIKONOMIKA, 2020)
Economic development in a country is indicated by an increase in the number of industrial sectors and other supporting facilities such as transportation. However, there is another impact on developments inndustrial sectors and transportation, especially environmental degradation. Air pollution is one of the environmental degradation. This research was conducted to determine the short-term and long-term environmental impact of industry and transport in Indonesia. The data analysis method in this research used Autoregressive Distribution Lag (ARDL) to see the short-term and long-term effects between research variables. The data used are data on CO2 emissions, the amount of industries and transport in Indonesia from 1965 - 2018. The results showed that the industry had a negative impact on increasing CO2 emissions in the short and long term. Meanwhile, transportation has a positive impact in the short term and a negative impact in the long term.